MOBİLYADA KALİTE BEKLENTİLERİ VE SATIN ALMAYI ETKİLEYEN FAKTÖRLER: NİTEL BİR ARAŞTIRMA - Tapinc, Mervan; Cavdar, Ertugrul (PressAcademia, 2022)
Purpose- Every individual develops a notion of quality in all goods, particularly furniture. Although quality perception varies by individual and product, when a large number of people are interviewed, we may get a sense of the overall quality impression. The purpose of this study is to find out what factors individuals consider while deciding on furniture quality and purchasing furniture.Methodology- In the online interview, the participants were asked questions such as why they find the furniture of high quality or poor quality, and what factors they pay attention to when purchasing furniture. A total of 50 participants were interviewed and their data was analyzed in the MAXQDA 2022 program.Findings- As a result of the analyzes made, 12 basic dimensions related to the quality of furniture were determined. These dimensions are according to the frequency of their mention; durability, material quality, comfort, aesthetics, usability and convenience as a sub-dimension, function, additional services, price, size, safety and perceived quality. As for the factors affecting purchasing, 11 basic dimensions have been identified. These are according to the frequency of mention; aesthetics, material quality, price, durability, comfort, usability, perceived quality, function, safety and size. When the word cloud was examined, words such as solid, long, comfortable, durable and useful were the most repetitive words. Istikbal, Bellona, Vivense and Ikea brands were the most mentioned brands, respectively. Since the evaluations of Istikbal and Bellona brands are all positive, it can be said that there is a high quality perception regarding these brands.Conclusion- As a result, when the quality perception of individuals in furniture is examined, it is seen that the most important element is durability, and the element they pay attention to when buying is aesthetics. In order to observe individuals' perceptions of quality in furniture, word frequencies were examined and the words "solid", "long", "comfortable", "useful" and "durable" came up. In terms of the brand, it was determined that Istikbal and Bellona had a positive perception of quality. Finally, it has been observed that the common understanding of quality for the majority of the participants increases in parallel with the lifetime of a product and its external appearance (design).

Amaç- Her birey, başta mobilya olmak üzere tüm ürünlerde kalite algısı geliştirir. Kalite algısı bireye ve ürüne göre değişmekle birlikte, çok sayıda kişiyle görüşüldüğünde, genel kalite izlenimi hakkında bir fikir edinebiliriz. Bu çalışmanın amacı, mobilya kalitesine karar verirken ve mobilya satın alırken bireylerin hangi faktörleri göz önünde bulundurduğunu belirlemektir.Yöntem- Online olarak gerçekleştirilen mülakat ile katılımcıların kaliteli ya da kalitesiz buldukları mobilyaları neden kaliteli ya da kalitesiz buldukları, ayrıca mobilya satın alırken hangi unsurlara dikkat ettikleri gibi sorular sorulmuştur. Toplam 50 katılımcı ile görüşülmüş ve verileri MAXQDA 2022 programında analiz edilmiştir.Bulgular- Yapılan analizler sonucunda mobilya kalitesi ile ilgili 12 adet temel boyut tespit edilmiştir. Bu boyutlar bahsedilme sıklıklarına göre; dayanıklılık, malzeme kalitesi, konfor, estetik, kullanışlılık ve alt boyutu olarak kolaylık, fonksiyon, ek hizmetler, fiyat, boyut, güvenlik ve algılanan kalitedir. Satın almayı etkileyen faktörler ile ilgili ise 11 temel boyut tespit edilmiştir. Bunlar değinilme sıklıklarına göre; estetik, malzeme kalitesi, fiyat, dayanıklılık, konfor, kullanışlılık, algılanan kalite, fonksiyon, güvenlik ve boyutudur. Kelime bulutu incelendiğinde, sağlam, uzun, rahat, dayanıklı ve kullanışlı gibi kelimeler en çok tekrar eden kelimeler olmuştur. Sırasıyla İstikbal, Bellona, Vivense ve Ikea markaları ise en çok değinilen markalar olmuştur. İstikbal ve Bellona markalarıyla ilgili değerlendirmelerin tamamı olumlu olması sebebiyle bu markalara ilişkin yüksek kalite algısının varlığından söz edilebilir.Sonuç- Sonuç olarak bireylerin mobilyadaki kalite algısı incelendiğinde en önemli unsurun dayanıklılık, satın alırken dikkat ettikleri unsurun ise estetik olduğu görülmüştür. Bireylerin mobilyadaki kalite algılarını gözlemlemek için sözcük frekansları incelendi ve "sağlam", "uzun", "rahat", "kullanışlı" ve "dayanıklı" kelimeleri karşımıza çıkmıştır. Marka açısından ise İstikbal ve Bellona’nın olumlu kalite algısına sahip olduğu belirlenmiştir. Son olarak katılımcıların büyük bir çoğunluğu için ortak kalite anlayışının, bir ürünün kullanım süresi ve dış görünüşüyle (tasarım) parallel olarak arttığı gözlemlenmiştir.
Keywords: Furniture; quality; product quality; buying behavior; perception of quality; Finans; İşletme; Mobilya; kalite; mamul kalitesi; satın alma davranışları; kalite algısı; Finance; Business Administration